Volatility modeling and asset pricing: Extension of GARCH model with macro economic variables, value-at- risk and semi-variance for KSE - Kashif Hamid; Arshad Hasan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2016)
The purpose of this study is to identify the behavior of returns and volatility with the attributes of non-linearities and asymmetric patterns in the returns series of KSE and modeling of volatility for asset pricing with macroeconomic, value at risk and semi-variance in GARCH specification. Daily data is used for stock returns for the period of Jan 2000 to Dec 2015 and the data for macroeconomic variables is taken for the period Jan 2000 to Dec 2015 on monthly basis. GARCH and GARCH- in- mean model is used for modeling the volatility in this study. GARCH-in-mean model is extended with macroeconomic variables in mean as well as with variance equation and findings indicate that the change in interest rate has significant negative effect on returns and increase in change in interest rate will decrease stock returns. The changes in oil prices have also significant positive impact on KSE returns. The results indicate that interest rate is significantly positively related to volatility. However oil prices change has also negative significant impact on volatility. It is concluded that macroeconomic variables are significant parameters for explaining the stock returns as well as volatility. Further GARCH (1, 1) Model is extended with Value at Risk in mean and variance equation. It is concluded that VaR is significantly negatively related to the returns of KSE market in GARCH specifications. Moreover GARCH (1,1) Model is extended with the Semi-variance for KSE. It is concluded that semi-variance is significant and indicates that downside risk has negative impact. In last study provides evidence that volatility influences returns in a non-linear fashion. This study provides an insight about the behavior of risk and return in emerging market of Pakistan which is prime area of interest for investors.
Keywords: 330; GARCH-in-Mean; macroeconomic variables; conditional volatility; value- at- risk; semi-variance; asymmetric patterns